2020
DOI: 10.1177/1559325820936124
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-377 Alleviates Myocardial Injury Induced by Hypoxia/Reoxygenation via Downregulating LILRB2 Expression

Abstract: Background: miR-377 is closely related to myocardial regeneration. miR-377-adjusted mesenchymal stem cells abducted ischemic cardiac angiogenesis. Nevertheless, there were rarely reports about the impact of miR-377 on myocardial ischemia injury. The purpose of this work is that whether miR-377 can protect against myocardial injury caused by hypoxia/reoxygenation (H/R). Methods: Gene expression omnibus database ( http://www.ncbi.nlm.nih.gov/geo/ ; no. GSE53211) was utilized to study the differential expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…33) As mentioned in the article, the up-regulation of miR-377 could significantly improve myocardial cell injury by targeting LILRB2 to regulate cell activity and apoptosis. 34) In our research, the outcomes illustrated that the miR-518a-5p expression was significantly down-regulated in MI, and we confirmed that the up-regulation of miR-518a-5p weakened GZMB expression by targeting the 3'-UTR of GZMB mRNA. Besides, miR-518a-5p could promote cell proliferation and suppress apoptosis by targeting GZMB so as to ameliorate H/R-induced HUVEC injury.…”
Section: Discussionsupporting
confidence: 74%
“…33) As mentioned in the article, the up-regulation of miR-377 could significantly improve myocardial cell injury by targeting LILRB2 to regulate cell activity and apoptosis. 34) In our research, the outcomes illustrated that the miR-518a-5p expression was significantly down-regulated in MI, and we confirmed that the up-regulation of miR-518a-5p weakened GZMB expression by targeting the 3'-UTR of GZMB mRNA. Besides, miR-518a-5p could promote cell proliferation and suppress apoptosis by targeting GZMB so as to ameliorate H/R-induced HUVEC injury.…”
Section: Discussionsupporting
confidence: 74%
“…When comparing HF diet exposed offspring to control samples, Rho family GTPase 1 (Rnd1), TNF receptor superfamily member 12A (Tnfrsf12a), heparin-binding EGF-like growth factor (Hbegf ) and a group of microRNAs, were discretely upregulated in addition to the aforementioned Fbln5. MicroRNAs are non-coding RNA, 19-24 nucleotides in length, that are known to regulate almost all biological processes, including glucose and lipid metabolism, apoptosis, signal transduction, and inflammatory responses (92). Specifically, mir323, mir539, mir377, and mir382 all demonstrate significant enrichment in samples taken from the HF diet groups.…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of myocardial infarction, mir539 expression increases significantly and binds to and inhibits the expression of MEK leading to impaired proliferation and apoptosis of cardiomyocytes ( 94 ). Mir377 also influences myocardial regeneration and angiogenesis by targeting many genes involved in inflammation, oxidative stress, and angiogenesis; converse to mir539 , it mitigates myocardial injury following ischemia-reperfusion injury by inducing angiogenesis and stem cell proliferation in ischemic myocardium ( 92 , 95 ). While no cardiac specific associations have been reported for mir382 , it has been observed to function as a PI3K/Akt pathway inhibitor ( 96 ) adding more relevance to network studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, hsa_circ_0001275 could sponge miR-377 in hFOB1.19 cells. Previous reports have confirmed that miR-377 participates in the development of various types of diseases [30,31]. In addition, miR-377 was reported to be involved in the dysfunction of osteoblasts [32,33].…”
Section: Plos Onementioning
confidence: 70%